The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5694/mja12.11665
|View full text |Cite
|
Sign up to set email alerts
|

Publicly funded homebirth in Australia: a review of maternal and neonatal outcomes over 6 years

Abstract: Conclusion:This study provides the first national evaluation of a significant proportion of women choosing publicly funded homebirth in Australia; however, the sample size does not have sufficient power to draw a conclusion about safety. More research is warranted into the safety of alternative places of birth within Australia. AbstractChristine Catling-Paull RN, RM, MMid, Lecturer in Midwifery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 30 publications
2
20
0
2
Order By: Relevance
“… 37 Rates of perineal lacerations were similarly low for planned home births in southern Australia (34.2% first to second degree, 1.1% third or fourth degree). 24 Rates of other maternal complications such as retained placenta or endometritis were also low in this home birth population. 24 In comparison with planned hospital birth, postpartum hemorrhage rates (>500 mL blood loss) are either the same 32 or lower in women who plan home birth, 26 , 27 and they are less likely to receive blood transfusion.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“… 37 Rates of perineal lacerations were similarly low for planned home births in southern Australia (34.2% first to second degree, 1.1% third or fourth degree). 24 Rates of other maternal complications such as retained placenta or endometritis were also low in this home birth population. 24 In comparison with planned hospital birth, postpartum hemorrhage rates (>500 mL blood loss) are either the same 32 or lower in women who plan home birth, 26 , 27 and they are less likely to receive blood transfusion.…”
Section: Resultsmentioning
confidence: 75%
“… 25 A descriptive study of publicly funded home birth in Australia reported a stillbirth and early neonatal death rate of 3.3/1,000, which was reduced to 1.7/1,000 when deaths related to fetal anomalies were excluded. 24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We created a study flow diagram to map out the number of records identified, included and excluded (Liberati 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Adrenaline interferes with the uptake of oxytocin at the myometrial receptor site (Gimpl and Farenholtz, 2001;Odent, 2001;Tortora and Grabowski, 2003;Stables and Rankin, 2005;Coad and Dunstall, 2011;Saxton et al, 2014) causing uterine atony. Midwifery models of care where midwives practice pronurturance demonstrate low rates of PPH (Dixon et al, 2009;Fahy et al, 2010;Catling-Paull et al, 2013). Maybe the hypermedicalization of birth (Simpson and Thorman, 2005;Zwelling, 2008;Rossen et al, 2010;Belghiti et al, 2011) is interfering with innate pronurturance behaviours at birth.…”
Section: Introductionmentioning
confidence: 94%